2021
DOI: 10.1109/access.2021.3132097
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter-Wave and Terahertz Fixed Wireless Link Budget Evaluation for Extreme Weather Conditions

Abstract: Date of publication xxxx 00, 0000, date of current version xxxx 00, 0000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Like water vapor in the atmosphere, the outcomes revealed that liquid water droplets, in the form of suspended particles in clouds, fogs, snowflakes, or rain falling hydrometeors, absorb or scatter the incident signals since their physical dimensions are in the same order as the THz wavelength. Such attenuation is not as strong as the path loss and atmospheric absorption but still needs to be taken into account for proper channel characterization [168].…”
Section: Weather Effectsmentioning
confidence: 99%
“…Like water vapor in the atmosphere, the outcomes revealed that liquid water droplets, in the form of suspended particles in clouds, fogs, snowflakes, or rain falling hydrometeors, absorb or scatter the incident signals since their physical dimensions are in the same order as the THz wavelength. Such attenuation is not as strong as the path loss and atmospheric absorption but still needs to be taken into account for proper channel characterization [168].…”
Section: Weather Effectsmentioning
confidence: 99%
“…This is due to their physical dimensions aligning with the scale of THz wavelengths. While this attenuation isn't as prominent as path loss or atmospheric absorption, it remains a crucial consideration for accurate channel characterization [14].…”
Section: Weather Effectsmentioning
confidence: 99%
“…Wind excitation induces fluctuating stresses on the tower leading to antenna tilting. This results in a beam deviation between transmitter and receiver, and then problems such as beam jitter will occur [21]. Therefore, wind-induced attenuation is also introduced into the loss assessment as one of the atmosphere-induced factors.…”
Section: Windmentioning
confidence: 99%
“…Parameter u is a variable related to signal wavelength, antenna diameter, and tilt angle [21]. For terahertz antennas, their diameters are set to be a common value of 0.16 m. Parameter J 1 refers to solving the first kind of Bessel function for the variable.…”
Section: Windmentioning
confidence: 99%